Benthic macroinvertebrates community as quality bioindicator of water in a sector of the Chotano river, Perú - Purihuamán-Leonardo, Celso Nazario (2022)
Two stations were established in a sector of the Chotano river, with the objective of evaluating the quality of the water, using benthic macroinvertebrates as bioindicators, for which biological indices were used: IBMWP, ETP %, diversity, richness, equity, dominance, density and trophic groups. The collection of macroinvertebrates was carried out using the Surber sampler, in two periods (dry and rainy). In the first season, an average of 710 ind/m2 were collected, classified in 23 taxa of the orders diptera, ephemeroptera and tricoptera, and in the second season 16790 ind/m2 were collected, with 6 taxa of the orders haplotaxide and diptera, the species indicating organic pollution, Chironomus sp, Tubbier sp and Psychoda sp, present mostly in season 2. The highest average indices in season 1 compared to season 2 were IBMWP with 60 points indicating moderately polluted doubtful water quality and 11 points indicating highly polluted critical quality, the diversity of Shannon - Wiener 1,33 and 0,30 indicating waters with limited diversity, the equity of  Pielou 0,50 show more stable and 0,20 less stable populations; the lowest indices in station 1 compared to season 2 were, Simpson dominance 0,37 indicator of low dominance and higher diversity and 0,9 indicator of higher dominance, lower diversity and higher organic pollution.